Integration of distributed energy storage into net-zero energy district systems: Optimum design and operation. (15th June 2018) - Sameti, Mohammad; Haghighat, Fariborz
Abstract: A net-zero energy district is any neighborhood where the consumption of the buildings is offset by on-building generation on an annual basis. In this study, a net-zero energy district is identified among the set of optimal solutions and the effects of storage on its performance is investigated. It is assumed the model simultaneously optimizes the location of host buildings (energy generators), type of technologies and associated size, and the energy distribution network layout together with the optimal operating strategy. The optimization model addresses all technologies with a special focus on the effect of application of energy storage. Two types of energy storage are considered inside each building: thermal energy storage (hot water tank) and electrical energy storage (battery bank). The model is applied to the new part of a district energy system located in Switzerland. The best integrated district energy systems are presented as a set of Pareto optimal solutions by minimizing both the total annualized cost and equivalent CO2 emission while ensuring the reliable system operation to cover the demand. The results indicated that selection of the proposed optimal district energy system along with the storage brings great economic and environmental benefits in comparison to all other scenarios (conventional energy system, stand-alone system, and net zero-energy without storage). Highlights: A multi-level procedure is proposed for energy optimization of a new district. Type, size, and location of the equipment are all taken into account. An optimal design of a net-zero energy district is presented with and without storage. A case study with seven buildings is presented to show the applicability of methodology. The results are compared to the optimal design of a stand-alone district.